2009
DOI: 10.14723/tmrsj.34.493
|View full text |Cite
|
Sign up to set email alerts
|

pH-Effect on Heavy-Metal Adsorption and Desorption of Sodium acrylate/Acrylamide and <i>p</i>-Styrenesulfonicacidsodiumsalt/Acrylamide Gels

Abstract: pH-dependences of Ni(II)-adsorbing and -desorbing properties of p-styrenesulfonicacidsodiumsalt/acrylamide (p-SSAS/AAm) and sodium acrylate/acrylamide (SA/AAm) gels have been investigated. Though the p-SSAS/AAm gel can capture more amount of Ni(II) even at a low pH region, its desorption ratio is below ~92 wt% even in 3 M of HCℓ concentration. On the other hand, though Ni(II)-capturing efficiencies of the SA/AAm gel is lower; its Ni(II)-desorption ratio is ~100 wt% in all the measured HCℓ concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Therefore, the authors also carried out a couple of consecutive measurements of adsorption by and desorption from respective positively [14,15,17,18,21] ionized hydrogels and negatively [19][20][21] polarized ones in order to examine the possibility of the reuse of the hydrogel; and it was demonstrated that these hydrogels can be satisfactorily utilized in the heavy-metal and rare-metal recycle. Though the utilization of hydrogels for the recovery of heavy metals and rare metals seems to be promising judging from the previous and present experimental results, however, the assumed conditions in these studies were still too simple compared with those in actual waste processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the authors also carried out a couple of consecutive measurements of adsorption by and desorption from respective positively [14,15,17,18,21] ionized hydrogels and negatively [19][20][21] polarized ones in order to examine the possibility of the reuse of the hydrogel; and it was demonstrated that these hydrogels can be satisfactorily utilized in the heavy-metal and rare-metal recycle. Though the utilization of hydrogels for the recovery of heavy metals and rare metals seems to be promising judging from the previous and present experimental results, however, the assumed conditions in these studies were still too simple compared with those in actual waste processing.…”
Section: Discussionmentioning
confidence: 99%
“…In the authors' previous studies, measured were the heavy metal capturing efficiencies both of the positively [9,10,17,18,21] and negatively [11][12][13][14][15][16][19][20][21] ionized hydrogels: The heavy-metal cation capturing efficiency of sodium acrylate/acrylamide (SA/AAm) and carboxymethylcellulose (CMC-Na) gels were found to be ~20 wt% of network polymer [9] [10,21]. As for the heavy-metal-anion capturing hydrogels [11][12][13][14][15][16][19][20][21], their capturing efficiencies are larger than those of SA/AAm and CMC-Na gels, which are much larger than those of zeolites and ion-exchange resins.…”
Section: Introductionmentioning
confidence: 99%
“…The first practical application of the multivalent-ion capturing property of the ionized hydrogel was made for developing the heavy-metal ion detector [6], however, the functionality of the detector utilizing the gel's multivalent-ion capturing property was only to indicate the ion species in the solvent by means of the difference in the volume phase transition temperature; there had not been the applications paying the attention to the multivalent-ion capturing amount. Under these circumstances, the authors have been investigating both of the adsorption and desorption properties of some hydrogels for the heavy-and/or rare-metal cations and anions aiming at the utilization for the environmental purification and the resource recycling [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the detector was not able to show how much the heavy-metal amount the gel can adsorb. In these circumstances, the authors have been focusing attention on the adsorbable quantity of the heavy-metal-capturing gels aiming at the realizetion of the high-efficient heavy-metal recovery gels [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the heavy-metal-cation capturing hydrogels, the authors have been also investigating heavy-metalanion capturing hydrogels because there are many harmful heavy-metal anions in the environment such as Cr 2 O 7 2-; and they found that some heavy-metal-anion adsorbing hydrogels show larger heavy-metal capturing efficiencies than SA/AAm and CMC-Na gels [9][10][11][12][13][14]. Moreover, recently, the authors demonstrated the possibility of the high-efficient heavy-metal-recycle process utilizing these hydrogels [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%